Sleep and restless legs syndrome in female adolescents with idiopathic musculoskeletal pain - Rita Aparecida Ribeiro Amorim; Gustavo A. Moreira; Flavia Heloisa Santos; Maria Teresa Terreri; Juliana Molina; Lívia de Freitas Keppeke; Simone Guerra Lopes da Silva; Melissa Mariti Fraga; Vanessa Bugni Miotto e Silva; Sergio Tufik; Claudio Arnaldo Len (Jornal de Pediatria (Versão em Português), 2020)
Objectives: To assess the presence of restless legs syndrome, periodic leg movement, and sleep disorders in female adolescents with idiopathic musculoskeletal pain through a sleep scale and polysomnography, and to compare these data in adolescents without pain history. Method: Twenty‐six adolescents diagnosed with idiopathic musculoskeletal pain followed in a pain outpatient clinic and 25 healthy controls matched by age and education were recruited. The restless legs syndrome criteria were evaluated according to the International Restless Legs Syndrome Study Group, the Sleep Disturbance Scale for Children was completed, nocturnal polysomnography was performed, and anxiety symptoms were recorded. Results: The mean age of idiopathic musculoskeletal pain adolescents was 13.9 ± 1.6 years; in controls, it was 14.4 ± 1.4 years. One adolescent in the control group (4%) and nine patients with idiopathic musculoskeletal pain (34.6%) fulfilled the restless legs syndrome criteria (p = 0.011). The authors did not observe significant differences in Sleep Disturbance Scale for Children scores between the groups in all components: disorders of initiating and maintaining sleep (p = 0.290), sleep breathing disorders (p = 0.576), disorders of arousal (p = 0.162), sleep‐wake transition disorders (p = 0.258), disorder of excessive daytime somnolence (p = 0.594), and sleep hyperhidrosis (p = 0.797). The neurophysiological, respiratory, and periodic leg movement parameters were similar in both groups. Having anxiety was not associated with restless legs syndrome (p = 0.11). Three patients with idiopathic musculoskeletal pain (11.5%) presented restless legs syndrome and periodic leg movement simultaneously, which was absent in the control group. Conclusion: Female adolescents with idiopathic musculoskeletal pain present criteria for RLS more frequently than healthy adolescents. However, this study did not observe relevant changes in objective and subject sleep variables. Resumo: Objetivos: Avaliar a presença de síndrome das pernas inquietas, movimento periódico das pernas e distúrbios do sono em adolescentes do sexo feminino com dor musculoesquelética idiopática por meio da escala do sono e da polissonografia e comparar esses dados em adolescentes sem histórico de dor. Método: Foram recrutados 26 adolescentes diagnosticados com dor musculoesquelética idiopática acompanhados em um ambulatório de dor e 25 controles saudáveis pareados por idade e escolaridade. Avaliamos os critérios da síndrome das pernas inquietas de acordo com o Grupo Internacional de Estudos de Síndrome das Pernas Inquietas, a Escala de Distúrbios do Sono em Crianças, a polissonografia noturna e os sintomas de ansiedade. Resultados: A idade média dos adolescentes com dor musculoesquelética idiopática foi 13,9 ± 1,6 anos e dos controles foi 14,4 ± 1,4 anos. Um adolescente no grupo de controle (4%) e nove pacientes com dor musculoesquelética idiopática (34,6%) atenderam aos critérios da síndrome das pernas inquietas (p = 0,011). Não observamos diferenças significativas nos escores da Escala de Distúrbios do Sono em Crianças entre os grupos em todos os componentes: distúrbios do início e da manutenção do sono (p = 0,290), distúrbios respiratórios do sono (p = 0,576), distúrbios do despertar (p = 0,162), distúrbios da transição sono‐vigília (p = 0,258), sonolência diurna excessiva (p = 0,594) e hiperidrose do sono (p = 0,797). Os parâmetros neurofisiológicos, respiratórios e o movimento periódico das pernas foram semelhantes nos dois grupos. Ansiedade não foi associada à síndrome das pernas inquietas (p = 0,11). Três pacientes com dor musculoesquelética idiopática (11,5%) apresentaram síndrome das pernas inquietas e movimento periódico das pernas simultaneamente, situação ausente no grupo de controle. Conclusão: As adolescentes do sexo feminino com dor musculoesquelética idiopática apresentaram critérios para síndrome das pernas inquietas com mais frequência do que as adolescentes saudáveis. Contudo, não observamos mudanças relevantes nas variáveis do sono objetivas e subjetivas.